INFLUENCE OF ACCOMMODATION ON FARROWING BEHAVIOUR IN LARGE WHITE YORKSHIRE GILTS - V. V. RAMESH SARAVANA KUMAR, V. RAMESH1 T. SIVAKUMAR (Indian Journal of Animal Production and Management, 2017)
An experiment was conducted to find out the different housing systems on thereproductive behaviour of pigs. Twenty four Large White Yorkshire pigs in the age group of 5months were selected and randomly divided into four groups consisting of 6 animals each.Among these, two groups were reared under intensive system and two groups under semiintensivesystem. From each system one group in individual housing and other group ingroup housing. All pregnant gilts under group housing both from intensive and Semiintensivesystem of management were transferred to farrowing crate, one week prior toexpected date of farrowing, whereas gilts under individual housing both from intensive andsemi-intensive system of management remained in the individual pen itself during farrowingand lactation. Farrowing behaviors were recorded from 3 days prior to farrowing andcontinued till the placenta was expelled. All the farrowing activities except straw wereperformed for significantly (P